Method for producing porous body

By replacing water in a gelled cellulose nanofiber dispersion with a t-butyl alcohol and water mixture and freeze-drying, the method addresses the issue of low transparency in cellulose porous materials, resulting in a highly transparent porous body with controlled fiber diameter.

JP2024177769APending Publication Date: 2024-12-24FUJIFILM CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023096100
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing methods for producing cellulose porous materials using cellulose nanofibers result in low transparency due to complete replacement of aqueous solvents with organic solvents like ethanol.

Method used

A method involving the replacement of water in a gelled cellulose nanofiber dispersion with a mixed solvent comprising t-butyl alcohol and water in a specific mass ratio, followed by freeze-drying, to produce a highly transparent porous body.

Benefits of technology

The method achieves a porous body with excellent transparency and a fiber diameter of 3 to 40 nm, preventing ice crystal growth and fiber aggregation during the freeze-drying process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177769000001
    Figure 2024177769000001
Patent Text Reader

Abstract

To provide a method for producing a porous body, which yields a porous body with superior transparency.SOLUTION: The present invention provides a method for producing a porous body with a fiber diameter of 3-40 nm, made from a cellulose nanofiber. This method includes: a step A for gelling a cellulose nanofiber water dispersion to form a gel; a step B for replacing the water in the gel with a mixed solvent of t-butanol and water in a mass ratio of 41:59 to 99:1; a step C for freezing the gel after step B to produce a frozen gel; and a step D for sublimation-drying the frozen gel.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a porous body. More specifically, the present invention relates to a method for producing a porous body using cellulose nanofibers as a raw material. [Background technology]

[0002] Cellulose nanofibers (hereinafter referred to as "CNF") are fibers produced from pulp and other cellulose-based raw materials through crushing and chemical processing. CNFs are lightweight and strong, and are expected to be used in a variety of applications. In addition, CNFs are natural materials derived from plants or living organisms, and are also attracting attention for their small environmental impact when disposed of. In addition, porous materials have been used for various purposes due to their structure, specific surface area, etc. Here, it is expected that porous cellulose materials containing CNFs will have the lightweight and high strength properties of CNFs.

[0003] The production of a porous cellulose body containing CNF is usually carried out by removing the dispersion medium from a dispersion containing CNF while preventing aggregation of the CNF. For example, Patent Document 1 describes a method in which an aqueous dispersion of cellulose nanofibers is gelled, the aqueous solvent contained in the gel is removed, and the gel is dried (see claims 1 and 3). In the examples, a method is described in which the aqueous solvent is replaced with ethanol, and then with t-butyl alcohol, followed by drying (see

[0106] ). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2012-001626 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present inventors have studied the method described in the examples of Patent Document 1 and have found that if the aqueous solvent is completely replaced with an organic solvent such as ethanol, a porous body with low transparency may be obtained, and that there is room for improvement.

[0006] Therefore, an object of the present invention is to provide a method for producing a porous body which can provide a porous body having excellent transparency. [Means for solving the problem]

[0007] As a result of intensive research to achieve the above-mentioned object, the inventors discovered that a highly transparent porous body can be obtained by replacing the water contained in a gelled product of an aqueous dispersion of cellulose nanofibers with a mixed solvent in which the mass ratio of t-butyl alcohol to water falls within a specific range, and then freeze-drying the mixture, thereby completing the present invention. That is, the present inventors have found that the above problems can be solved by the following configuration.

[0008] [1] A method for producing a porous body having a fiber diameter of 3 to 40 nm using cellulose nanofibers as a raw material, comprising the steps of: A step A of gelling the aqueous dispersion of cellulose nanofibers to obtain a gelled product; A step B of replacing the water contained in the gelled product with a mixed solvent having a mass ratio of t-butyl alcohol and water of 41:59 to 99:1; A step C of freezing the gelled product obtained after the step B to obtain a frozen gelled product; and D. sublimation drying the frozen gelled material. [2] The method for producing a porous body according to [1], wherein a mass ratio of t-butyl alcohol to water in the mixed solvent is 60:40 to 99:1. [3] The method for producing a porous body according to [1], wherein the mass ratio of t-butyl alcohol to water in the mixed solvent is 85:15 to 95:5. Effect of the Invention

[0009] According to the present invention, there is provided a method for producing a porous body, which can provide a porous body having excellent transparency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention will be described in detail below. The following description of the configuration may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment.

[0011] The following describes the meaning of each description in this specification. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0012] <Method of manufacturing porous body> The method for producing a porous body of the present invention (hereinafter abbreviated as "the production method of the present invention") is a method for producing a porous body having a fiber diameter of 3 to 40 nm using cellulose nanofibers (CNF) as a raw material. Furthermore, the method for producing a porous body of the present invention includes step A of gelling an aqueous dispersion of cellulose nanofibers to obtain a gelled material, step B of replacing the water contained in the gelled material with a mixed solvent (hereinafter also abbreviated as "specific mixed solvent") having a mass ratio of t-butyl alcohol (hereinafter also abbreviated as "TBA") and water (TBA:water) of 41:59 to 99:1, step C of freezing the gelled material after step B to obtain a frozen gelled material, and step D of sublimating and drying the frozen gelled material.

[0013] In the manufacturing method of the present invention, as described above, the water contained in the gelled product of the aqueous dispersion of cellulose nanofibers is replaced with a specific mixed solvent, and then freeze-dried, thereby making it possible to obtain a highly transparent porous body. The reason why this effect is manifested is not clear in detail, but the present inventors speculate as follows. First, in Comparative Examples 2 and 3 described later, it is shown that when a mixed solvent of TBA:water of 39:61 or a solvent of TBA:water of 100:0 is used as a solvent to replace water, the fiber diameter of the resulting porous body becomes large and the permeability becomes low. Therefore, in the manufacturing method of the present invention, by replacing with a specific mixed solvent, the gelled product after replacement contains a specific amount of water, and the inventors have found that the presence of this water makes the ice crystals formed when TBA freezes much smaller than when TBA alone is used, and prevents the aggregation of fibers due to ice crystal formation. As a result, it is presumed that the fiber diameter of the porous body obtained after freeze-drying is in the range of 3 to 40 nm, and transparency is expressed. Each step used in the production method of the present invention will now be described in detail.

[0014] [Process A] Step A in the production method of the present invention is a gelation step in which an aqueous dispersion of cellulose nanofibers is gelled to obtain a gelled product. Here, the aqueous dispersion of cellulose nanofibers refers to a dispersion liquid in which cellulose nanofibers are dispersed in a dispersion medium containing at least water, and can be obtained by the method for preparing cellulose nanofibers described below.

[0015] (Cellulose nanofiber) The cellulose nanofibers (CNF) contained in the cellulose nanofiber aqueous dispersion are not particularly limited, and any known CNF can be used. CNF refers to a material in which two or more cellulose molecular chains are bundled together. The term "cellulose molecular chains bundled together" refers to a state in which two or more cellulose molecular chains are assembled to form an aggregate called a microfibril. CNF is generally obtained by processing plant-derived fibers. The raw material of CNF is not particularly limited, and examples thereof include plant-derived fibers contained in wood, bamboo, hemp, jute, kenaf, cotton, beet pulp, potato pulp, agricultural waste, cloth, and paper. As the raw material of CNF, these may be used alone or in combination of two or more.

[0016] The CNF may be chemically modified, and chemically modified CNF is preferred in that the permeability of the resulting porous body is easily increased. In chemically modified CNF, some or all of the groups in the cellulose molecular chain are changed by chemical treatment. For example, the cellulose molecular chain in chemically modified CNF has some or all of the hydroxyl groups at C6 in the molecule oxidized to aldehyde groups, carboxyl groups, etc., some or all of the hydroxyl groups including those at the C6 position are oxidized, esterified such as nitrate ester, acetate ester, phosphate ester, and etherified such as methyl ether, hydroxypropyl ether, carboxymethyl ether, etc., and replaced with other functional groups. More specifically, examples of groups introduced by chemical modification include a carboxy group, an acetyl group, a sulfate group, a sulfonic acid group, an acryloyl group, a methacryloyl group, a propionyl group, a propioloyl group, a butyryl group, a 2-butyryl group, a pentanoyl group, a hexanoyl group, a heptanoyl group, an octanoyl group, a nonanoyl group, a decanoyl group, an undecanoyl group, a dodecanoyl group, a myristoyl group, a palmitoyl group, a stearoyl group, a pivaloyl group, a benzoyl group, a naphthoyl group, a nicotinoyl group, an isopropyl group, a phenyl ... Examples of such alkyl groups include acyl groups such as sonicotinoyl, furoyl, and cinnamoyl groups; isocyanate groups such as 2-methacryloyloxyethylisocyanoyl groups; alkyl groups such as methyl, ethyl, propyl, 2-propyl, butyl, 2-butyl, tert-butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, myristyl, palmityl, and stearyl groups; oxirane, oxetane, thiirane, and thietane groups. Among these, it is preferable that the group introduced by chemical modification contains at least a carboxy group.

[0017] The chemical modification of CNF can be carried out by a conventional method. That is, cellulose can be chemically modified by reacting it with a chemical modifying agent. If necessary, a solvent or a catalyst may be used, or heating or decompression may be performed. The types of chemical modifiers include acids, acid anhydrides, alcohols, halogenating agents, alcohols, isocyanates, alkoxysilanes, cyclic ethers such as oxiranes (epoxies), etc. These may be used alone or in combination of two or more. Examples of the acid include acetic acid, acrylic acid, methacrylic acid, propanoic acid, butanoic acid, 2-butanoic acid, and pentanoic acid. After the chemical modification, it is preferable to wash thoroughly with water to terminate the reaction. It is also preferable to further replace the organic solvent such as alcohol after washing thoroughly with water. In this case, the cellulose is replaced by immersing it in an organic solvent such as alcohol.

[0018] The average fiber diameter of the CNF is not particularly limited, but is preferably 1 to 100 nm, more preferably 2 to 50 nm, and even more preferably 2 to 10 nm. By using CNF with an average fiber diameter of 1 to 100 nm, it is easy to obtain a porous body with a large specific surface area. When the average fiber diameter is 1 nm or more, the single fiber strength of the nanofiber is large, and the structure of the porous body is easily maintained. Here, the average fiber diameter is calculated as follows. An electron microscope image of the CNF is obtained using a transmission electron microscope (TEM) or a scanning electron microscope (SEM). Two random axes are drawn vertically and horizontally for each image obtained, and the fiber diameters of the fibers intersecting the axes are visually read. This is done at a magnification of 5000x, 10000x, or 50000x depending on the size of the fibers constituting the image. The sample or magnification is set so that 20 or more fibers intersect the axis. In this way, at least three images of the non-overlapping surface portion are taken with the electron microscope, and the fiber diameter values ​​of the fibers intersecting each of the two axes are read. Therefore, at least 20 x 2 x 3 = 120 pieces of fiber information are obtained. The number average fiber diameter is calculated from the fiber diameter data obtained in this way, and is taken as the average fiber diameter of the CNF. For branched fibers, if the length of the branched portion is 50 nm or more, it is included in the calculation of the fiber diameter as a single fiber.

[0019] Furthermore, the average fiber length of the CNF is not particularly limited, but is preferably 0.01 to 20 μm, and more preferably 0.05 to 10 μm. The average fiber length is calculated by casting a thin layer of CNF aqueous dispersion on a substrate, freeze-drying the sample, and observing it with an SEM. From the obtained observation image, 10 independent fibers are randomly selected per image, and their fiber lengths are read visually. This is done at a magnification of 5000x or 10000x depending on the length of the fibers that compose the image. The sample or magnification is one in which the start and end points of the fibers are within the same image. In this way, at least 12 non-overlapping surface parts are observed with an SEM, and the fiber lengths are read. Therefore, at least 10 fibers x 12 sheets = 120 fiber information is obtained. The number average fiber length is calculated from the fiber diameter data obtained in this way, and is taken as the average fiber length of the CNF. For branched fibers, the length of the longest part of the fiber is taken as the fiber length.

[0020] The method for adjusting the average fiber diameter of CNF is not particularly limited, but for example, in the mechanical crushing method, it is possible to adjust the processing time and number of times of the ultra-high pressure homogenizer or grinder used. In addition, in the chemical crushing method, it is possible to adjust the type of oxidizing agent (e.g., sodium hypochlorite, etc.), the concentration of the catalyst (e.g., TEMPO (2,2,6,6-tetramethyl-1-piperidinyloxy) catalyst, etc.), and the reaction time.

[0021] The method for preparing CNF is not particularly limited, but a mechanical or chemical crushing method is preferred. Examples of mechanical disintegration methods include methods in which an aqueous suspension or slurry of cellulose fiber-containing material is mechanically ground or beaten using a refiner, high-pressure homogenizer, grinder, single-axis or multi-axis kneader, bead mill, or the like to disintegrate the material. Examples of mechanical processing methods include those described in Japanese Patent No. 5500842, Japanese Patent No. 5283050, Japanese Patent No. 5207246, Japanese Patent No. 5170193, Japanese Patent No. 5170153, Japanese Patent No. 5099618, Japanese Patent No. 4845129, Japanese Patent No. 4766484, Japanese Patent No. 4724814, Japanese Patent No. 4721186, Japanese Patent No. 4428521, International Publication No. 11 / 068023, Japanese Patent No. 5477265, and JP-A-2014-84434. On the other hand, as a chemical disintegration method, for example, a cellulose-based raw material is oxidized with an oxidizing agent in the presence of an N-oxyl compound and a bromide and / or iodide, and the oxidized cellulose is further defibrated by wet micronization to produce nanofibers. Examples of chemical processing methods include those described in Japanese Patent No. 5381338, Japanese Patent No. 4981735, Japanese Patent No. 5404131, Japanese Patent No. 5329279, Japanese Patent No. 5285197, Japanese Patent No. 5179616, Japanese Patent No. 5178931, Japanese Patent No. 5330882, and Japanese Patent No. 5397910.

[0022] The dispersion medium in the CNF aqueous dispersion is not particularly limited as long as it contains at least water, but it preferably contains 70% by mass or more of water relative to the total mass of the dispersion medium, more preferably contains 90% by mass or more, and even more preferably contains 99% by mass or more. The dispersion medium in the CNF aqueous dispersion may be water. The content of CNF in the CNF aqueous dispersion is preferably 0.001 to 5 mass %, more preferably 0.01 to 2 mass %, and even more preferably 0.1 to 1 mass %, based on the total mass of the CNF aqueous dispersion.

[0023] Before being subjected to step A, the CNF aqueous dispersion may be subjected to defibration treatment, treatment to remove coarse fibers, and concentration treatment. The defibration treatment is a treatment for loosening the fibers of CNF, and examples of the method include a method of applying a mechanical shear force. Specific examples of the defibration treatment method include a treatment using a mixer and a treatment using ultrasonic waves. The coarse fiber removal process is a process for removing coarse fibers contained in the CNF aqueous dispersion, and examples of the process include filtering and classification. A specific example of the classification process is centrifugal classification.

[0024] The CNF aqueous dispersion may further contain an antifreeze agent. The antifreeze agent refers to an agent that has a function of suppressing the freezing of water, and is not particularly limited, and any known antifreeze agent can be used. Examples of antifreeze agents include water-soluble polymers, sugars, and antifreeze proteins, and among these, antifreeze proteins are preferred. The antifreeze agent has the effect of suppressing the growth of ice crystals and can suppress the coarsening of ice crystals. When the aqueous dispersion contains an antifreeze agent, the ice crystals are not coarsened during freeze-drying, so the fiber diameter of the resulting porous body tends to be narrow.

[0025] Examples of water-soluble polymers that serve as antifreeze agents include polyvinyl alcohol, polyvinylpyrrolidone, and polyethylene glycol.

[0026] Examples of sugars as antifreeze agents include glucose, maltose, sucrose, lactose, trehalose, raffinose, etc. Polysaccharides extracted from fungi (e.g., Flammulina velutipes) are also preferred.

[0027] Examples of antifreeze proteins include antifreeze glycoproteins and antifreeze proteins. The antifreeze proteins may have the effect of suppressing the growth of ice crystals, and may be extracted and purified from natural resources such as fish, plants, insects, and fungi, or may be produced using bacterial culture and genetic recombination technology or chemical synthesis. Among these, the antifreeze proteins are preferably fish-derived antifreeze proteins, in that the resulting porous body has excellent transparency.

[0028] Antifreeze proteins exist in a wide variety of forms, differing in amino acid composition and higher-order structure. For example, antifreeze proteins derived from fish include type I antifreeze proteins with a molecular weight of approximately 3,000 to 5,000 consisting of an alpha helix structure mainly containing Ala (alanine); type II antifreeze proteins with a molecular weight of approximately 14,000 to 24,000 consisting of a structural motif similar to that of a type lectin; type III antifreeze proteins with a molecular weight of approximately 7,000 consisting of a globular structure containing multiple β structures; type IV antifreeze proteins with a molecular weight of approximately 12,000 consisting of a structure of bundled alpha helices; and antifreeze glycoproteins (AFGPs) with a molecular weight of approximately 3,000 to 24,000 consisting of a repeating structure of the three residues -Ala-Thr (threonine)-Ala-, in which the side chain of the Thr residue is glycosylated. Other preferred antifreeze proteins include insect-derived antifreeze proteins having a β-helix structure and a molecular weight of about 7000 to 12000, and antifreeze proteins derived from radish sprouts.

[0029] It is preferable that the antifreeze agent exhibits thermal hysteresis. Thermal hysteresis is defined as the value (°C) obtained by subtracting the freezing temperature (°C) from the equilibrium melting point (°C) shown below, and the presence of thermal hysteresis means that this value is 0.05°C or more. The greater the thermal hysteresis, the greater the ability of the agent as an antifreeze agent, since the growth of ice crystals can be suppressed to a lower temperature. The freezing temperature refers to the temperature at which ice crystals start to grow when an aqueous solution containing an antifreeze is cooled to a temperature below the freezing point of water. The equilibrium melting point is the temperature at which melting begins when the temperature of an aqueous solution containing a completely frozen antifreeze is raised. The antifreeze agent exhibits thermal hysteresis, the value of which is preferably 0.1° C. or more, more preferably 0.4° C. or more, even more preferably 0.5° C. or more, particularly preferably 0.9° C. or more, and most preferably 1.0° C. or more. The upper limit of the thermal hysteresis value is not particularly limited, but may be, for example, 10° C. When the thermal hysteresis value of the antifreeze agent is within the above preferred range, the transparency of the obtained porous body is more excellent.

[0030] The content of the antifreeze agent in the CNF aqueous dispersion is preferably adjusted to be 1 to 40 mass%, and more preferably 10 to 30 mass%, relative to the total mass of the components other than the dispersion medium in the CNF aqueous dispersion. Specifically, for example, the content of the antifreeze agent in the CNF aqueous dispersion is preferably 0.0001 to 0.8 mass %, and more preferably 0.001 to 0.4 mass %, based on the total mass of the CNF aqueous dispersion.

[0031] The CNF aqueous dispersion may contain additives other than CNF and antifreeze agents. Additives include, for example, water repellent components and strength modifiers.

[0032] The water-repellent component refers to a component capable of imparting water-repellent function, and any known water-repellent component can be used. Examples of the water-repellent component include fluorine-based water-repellent, silicone-based water-repellent, wax-based water-repellent, alkylketene dimer, and hydrolysis condensate of alkoxysilane. Examples of the generating component include surfactants. Here, the surfactant refers to a compound having a hydrophobic group and a hydrophilic group in the molecule. Among them, the water-repellent component is preferably a compound having a fluorinated alkyl group. The fluorinated alkyl group may be a partially fluorinated alkyl group or a perfluoroalkyl group. The number of carbon atoms in the fluorinated alkyl group is preferably 1 to 20, more preferably 2 to 16, and further preferably 4 to 12. The number of carbon atoms in the fluorinated alkyl group refers to the number of carbon atoms to which fluorine atoms are bonded, and carbon atoms to which no fluorine atoms are bonded are not included in the number of carbon atoms in the fluorinated alkyl group.

[0033] The content of the water-repellent component is preferably from 0.001 to 10 mass %, and more preferably from 0.01 to 5 mass %, based on the total mass of the components other than the dispersion medium in the CNF aqueous dispersion. The water-repellent component may be used alone or in combination of two or more. When two or more water-repellent components are used in combination, the total content is preferably within the above-mentioned preferred range.

[0034] Examples of strength modifiers include various latex emulsions such as acrylic latex, NBR latex, vinyl acetate latex, and olefin latex, as well as water-soluble polymers such as polyacrylamide, polyamide epichlorohydrin, polyvinyl alcohol, and starch. The content of the strength modifier is preferably 5 mass % or less, and more preferably 1 mass % or less, based on the total mass of the components other than the dispersion medium in the CNF aqueous dispersion. The CNF aqueous dispersion does not need to contain the above-mentioned additives.

[0035] In step A, the CNF aqueous dispersion is gelled. The method for gelling the CNF aqueous dispersion is not particularly limited, but examples include a method of adding an acidic or alkaline component, and the method of adding an acidic component is preferred. By adding the above component, the electrostatic repulsive force that contributes to the dispersion of CNFs in the CNF aqueous dispersion is weakened, and a CNF network is formed, so that the CNF aqueous dispersion gels and a gelled product is obtained. The acidic component to be added is not particularly limited, but examples thereof include inorganic acids (e.g., hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid), organic acids (e.g., methanesulfonic acid, tosylic acid), and metal halides (e.g., aluminum chloride). In addition, it is preferable to add the acidic component to the CNF aqueous dispersion in the form of a solution. The amount of the acidic component added can be adjusted as appropriate, but it is preferable to add the acidic component in an amount of 0.01 to 5 mol / L relative to the total volume of the CNF aqueous dispersion after the addition of the acidic component. When the acidic component is added, it is also preferable to add the acidic component without forcibly stirring it and then leave it to stand. The time for leaving it to stand is not particularly limited as long as a gel is obtained, but it is preferably 0.1 to 12 hours, more preferably 0.5 to 3 hours.

[0036] When gelling the CNF aqueous dispersion, it is preferable to mold the CNF aqueous dispersion into a desired shape and gel it. As a method for molding the CNF aqueous dispersion into a desired shape, a method of placing the CNF aqueous dispersion in a container having a desired shape can be mentioned. The shape of the gel obtained by gelling the CNF aqueous dispersion is not particularly limited, but a sheet shape is preferred. The sheet shape means a shape having two opposing main surfaces, a thickness smaller than the main surfaces, and a flat shape overall. The main surfaces do not need to be completely flat. The ratio of the thickness of the gel to the maximum length in the in-plane direction of the main surface of the sheet-like gel is preferably 0.5 or less, more preferably 0.3 or less. The lower limit of the ratio is not particularly limited, but may be 0.00001 or more, and is often 0.001 or more. The shape of the sheet-like gelled material when viewed in the normal direction of the main surface is not particularly limited and may be any shape, for example, a square, polygonal, circular, or elliptical shape. The maximum length in the in-plane direction of the main surface of the sheet-like gelled material is preferably from 1 cm to 2 m, and more preferably from 10 cm to 1 m. The main surface area of ​​the sheet-like gel is 2 cm 2 ~5m 2 is preferred, and 100 cm 2 ~1m 2 is more preferred.

[0037] In the manufacturing method of the present invention, as described above, the CNF aqueous dispersion may be molded into the desired shape during gelation, or after obtaining the gelled material, it may be processed into the desired shape and then subjected to step B described below.

[0038] [Process B] Step B of the production method of the present invention is a solvent substitution step in which the water contained in the gelled material obtained in step A is substituted with a mixed solvent (specific mixed solvent) in which the mass ratio of t-butyl alcohol (TBA) and water (TBA:water) is 41:59 to 99:1.

[0039] In the present invention, because a porous body with higher transparency can be obtained, the mass ratio of TBA to water (TBA:water) in the specific mixed solvent is preferably 60:40 to 99:1, more preferably 70:30 to 99:1, even more preferably 85:15 to 95:5, and particularly preferably 88:12 to 92:8.

[0040] The method of solvent replacement is not particularly limited, and examples thereof include a method of immersing the gelled material in a specific mixed solvent; a method of continuously supplying the specific mixed solvent to the gelled material; and the like. Among these, the method of immersing the gelled product in the specific mixed solvent is preferred, and the method of shaking the gelled product while immersing it in the specific mixed solvent is more preferred. The gelled material may be immersed in the specific mixed solvent multiple times (e.g., 2 to 10 times) by changing the specific mixed solvent to be immersed in. In this case, the gelled material may be immersed multiple times in the specific mixed solvent in which the mass ratio of TBA to water (TBA:water) is gradually changed to the desired mass ratio. The immersion time of the gelled material in the specific mixed solvent (the immersion time for each immersion in the case of multiple immersions) is not particularly limited as it can be appropriately adjusted depending on the shape of the gelled material, but is preferably 1 to 48 hours, and more preferably 1 to 24 hours.

[0041] [Process C] Step C in the production method of the present invention is a step of freezing the gelled material obtained after step B to obtain a frozen gelled material. Here, the gelled material can be frozen by cooling it to a temperature below the freezing point of the solvent component contained in the gelled material, and can be frozen by a known method. Among them, freezing by rapid cooling is preferable, since the ice crystals of the solvent generated when the solvent component freezes are less likely to become large and the fiber diameter of the resulting porous body is smaller. A method for rapid cooling includes, for example, contacting with liquid nitrogen, and specifically, a preferred method is immersion in liquid nitrogen.

[0042] [Process D] Step D in the production method of the present invention is a step of sublimating and drying the frozen gelatinous material. Here, sublimation drying refers to a process in which a solid of the solvent component (the specific mixed solvent described above) contained in the frozen gelled material is desorbed as a gas from the frozen gelled material. In addition, the sublimation drying is preferably carried out in an environment below the freezing point of the solvent component contained in the frozen gel. In addition, in order to improve the sublimation rate, it is also preferable to carry out the sublimation drying in a reduced pressure environment where the pressure is lower than atmospheric pressure. When the sublimation drying is carried out in a reduced pressure environment, the pressure is preferably 0.01 to 10,000 Pa, more preferably 0.1 to 1,000 Pa, and even more preferably 10 to 100 Pa. The time for sublimation drying can be appropriately adjusted depending on the shape of the frozen gelled product, but is usually carried out for about 1 to 48 hours.

[0043] In the manufacturing method of the present invention, a porous body having a fiber diameter of 3 to 40 nm is obtained through the above-mentioned steps A to D.

[0044] [Fiber diameter of porous body] The porous body obtained by the porous body manufacturing method of the present invention (hereinafter also formally abbreviated as "porous body of the present invention") is a porous body made from cellulose nanofiber (CNF) and has a fiber diameter of 3 to 40 nm. In this specification, the fiber diameter of the porous body is measured by small angle X-ray scattering (SAXS). Specifically, first, X-rays are incident on the porous body to obtain a pre-treatment scattering curve. The scattering intensity in this pre-treatment scattering curve is normalized based on the incident X-ray intensity transmitted through a beam stopper to obtain a normalized scattering curve for the porous body. A blank measurement is also performed to obtain a normalized scattering curve for the medium (air) in the same manner. The normalized scattering curve for the medium is subtracted from the normalized scattering curve for the porous body to obtain a scattering curve I(q) for the fibers constituting the porous body. Here, q is the scattering vector calculated using the scattering angle 2θ from the following equation: q = 4*π*(sin(θ)) / λ (π: Pi, 2θ: Scattering angle [rad], λ: X-ray wavelength [nm]) When the scattering curve I(q) of the obtained porous body is plotted on a log-log graph, a region appears where the slope is linear. For this region, a Guinier plot is made for the cross section, and the scattering intensity average fiber diameter Dc is calculated using the following formula: q*I(q) ∝ exp(-(Dc2 * q2) / 16) The scattering intensity average fiber diameter Dc calculated by the above formula is defined as the fiber diameter of the porous body.

[0045] The fiber diameter of the porous body of the present invention is, as described above, 3 to 40 nm or less, but is preferably 4 to 30 nm, more preferably 10 to 25 nm, in terms of superior transparency of the porous body. The fiber diameter of the porous body can be adjusted, for example, by the fiber diameter and type of CNF used, and the conditions of each step in the manufacturing method of the porous body of the present invention.

[0046] In the porous body of the present invention, the CNF content is preferably 80 mass % or more, more preferably 90 mass % or more, and even more preferably 95 mass % or more, based on the total mass of the porous body.

[0047] <Application> The porous body of the present invention has high transparency and can be applied to various applications. For example, it can be suitably applied to applications in which it is required to transmit light while exerting a heat insulating effect. Specifically, the porous body of the present invention can be suitably applied to windows or components thereof. That is, the porous body of the present invention can be used as a transparent heat insulating material, and the transparent heat insulating material can be suitably applied to windows or components thereof. Specific examples of the application of the porous body of the present invention to windows will be described below, but the uses of the porous body of the present invention are not limited to the following specific examples.

[0048] [Laminated glass] The porous body of the present invention can be used as an interlayer film for laminated glass. The structure of the laminated glass is not particularly limited, and a known structure can be used. For example, the number of glass plates used in the laminated glass may be two or more, may be three or more, or may be four or more. When the porous body of the present invention is used as an interlayer film for laminated glass, it will be disposed between two or more glass plates used in the laminated glass. When the number of glass plates is three or more, the porous body of the present invention may be disposed between each of the glass plates, or the porous body of the present invention may be disposed only between one pair of glass plates.

[0049] When the porous body of the present invention is used as an interlayer film of laminated glass, a configuration (another layer) other than the porous body of the present invention may be present between a pair of glass plates. That is, the porous body of the present invention provided between the glass plates may be in direct contact with the glass plates or may be in contact with the glass plates via another layer. Preferred examples of the other layer include one or more resin layers selected from the group consisting of polyvinyl butyral, polycarbonate, ethylene-vinyl acetate copolymer, and polyethylene terephthalate. The other layer preferably includes an adhesive layer or a pressure-sensitive adhesive layer. Further, other layers described later in the description of insulating glass may be applied to the laminated glass.

[0050] The glass plates used in the laminated glass can be any known glass depending on the purpose, and examples thereof include transparent glass plates, patterned glass plates, wired glass plates, lined glass plates, tempered glass plates, heat reflecting glass plates, heat absorbing glass plates, Low-E glass plates, and various other glass plates. In addition, one or more of the glass plates used in the laminated glass may be made of a glass substitute resin such as polycarbonate. The thickness of the glass plates can be appropriately selected depending on the purpose. The shape of the glass plate is not particularly limited and can be appropriately adjusted depending on the application. The glass plate may have a curved surface.

[0051] The laminated glass may have a known sealing structure, for example, a structure in which the outer edge of the laminated glass is sealed with a sealant such as a resin.

[0052] [Double glazing] The porous body of the present invention can be applied to insulating glass. Insulating glass refers to glass that contains a gas layer between two or more glass sheets. The gas layer is a layer made of gas, and the gas contained in the gas layer may be air or an inert gas such as nitrogen gas or argon gas. The gas layer may be at a pressure lower than atmospheric pressure. The number of glass plates contained in the insulating glass may be two or more, may be three or more, or may be four or more. When the porous body of the present invention is applied to insulating glass, the porous body of the present invention will be placed between a pair of glass plates. When the number of glass plates is three or more, the porous body of the present invention may be placed between each of the glass plates, or the porous body of the present invention may be placed only between one pair of glass plates.

[0053] When the porous body of the present invention is used in insulating glass, it may have one or more components (other layers) other than the porous body of the present invention. The other layers include, in addition to the layers described above, a light-shielding layer, a heat-shielding layer, and the like. The light-shielding layer may be a layer having a low transmittance for at least a part of visible light, or may be a layer having a low transmittance for at least a part of ultraviolet light. Examples of the light-shielding layer include a metal vapor deposition film and a colored layer such as a dye layer containing a dye. The heat shield layer may be a layer that reflects or absorbs infrared rays, and examples of such a layer include a metal vapor deposition film, a polymer layer containing metal particles or metal oxide particles, and a dielectric multilayer film. The other layers include a flame retardant layer. The flame retardant layer includes a layer containing a flame retardant, and known flame retardants can be used as the flame retardant. Examples of the flame retardant include aromatic phosphate esters, phosphorus compounds such as red phosphorus, halogen compounds such as chlorinated paraffin containing at least one of chlorine and bromine, antimony compounds such as antimony trioxide, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, and nitrogen compounds such as melamine cyanurate.

[0054] The glass plate may be any of the glass plates used in the above-mentioned laminated glass. The glass sheets included in the insulating glass may be laminated glass. The laminated glass may be laminated glass containing the porous body of the present invention described above.

[0055] The insulating glass may have a known sealing structure. For example, the sealing structure may be a sealing structure using a spacer disposed on the outer edge of a pair of glass sheets and a sealant disposed between the spacer and the glass sheet facing the spacer. The above-mentioned sealing structure allows the space formed by the pair of glass sheets and the spacer to become the above-mentioned gas layer. The spacer may contain a desiccant for the purpose of absorbing moisture from the above-mentioned gas layer. The glass plate may be sealed at its outer edge side beyond the spacer with another sealant, such as a curable resin such as a polysulfide resin or a silicone resin. The sealing structure may also be constituted by a frame that holds the insulating glass.

[0056] When the porous body of the present invention is applied to the above-mentioned laminated glass and double glazing, an integrally molded porous body may be applied, or a plurality of porous bodies may be applied by arranging them in the planar direction of the glass sheets. Also, a plurality of porous bodies may be applied by stacking them in the lamination direction of the glass sheets. When the porous body of the present invention is applied to the above-mentioned laminated glass and insulating glass, the above-mentioned flame retardant may be added to the porous body.

[0057] The above-mentioned laminated glass and double glazing can be suitably used, for example, as windows for houses and windows for vehicles such as passenger cars. In addition, the above-mentioned laminated glass and insulating glass are capable of transmitting radio waves because the porous body of the present invention does not have electrical conductivity. When it is desired to transmit radio waves, it is preferable to select a layer that does not have electrical conductivity as the above-mentioned other layer. EXAMPLES

[0058] The present invention will be described in further detail below with reference to examples. The materials, amounts, ratios, processing contents, processing procedures, etc. shown in the following examples can be changed as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following examples.

[0059] <Example 1> [Preparation process of cellulose nanofiber aqueous dispersion] 2.00 g of NBKP (kraft pulp made from bleached softwood raw materials, mainly consisting of fibers with a diameter exceeding 1000 nm) in a dry weight equivalent, 0.025 g of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxy radical), and 0.25 g of sodium bromide were dispersed in 150 ml of water, and then a 13% aqueous solution of sodium hypochlorite was added to 1.00 g of NBKP so that the amount of sodium hypochlorite was 5.00 mmol, to initiate the reaction. During the reaction, a 0.50 mol / L aqueous solution of sodium hydroxide was added dropwise to maintain the pH at 10. After reacting for 2 hours, the reaction product was filtered and thoroughly washed with water to obtain an oxidized cellulose slurry. A 0.15% by mass oxidized cellulose slurry was defibrated for 5 minutes at 15,000 rpm using a biomixer (BM-2, manufactured by Nippon Seiki Seisakusho Co., Ltd.), and then further defibrated for 20 minutes using an ultrasonic disperser (model US-300E, manufactured by Nippon Seiki Seisakusho Co., Ltd.). After that, coarse fibers were removed by centrifugation to obtain a transparent cellulose nanofiber aqueous dispersion. The obtained cellulose nanofiber aqueous dispersion was concentrated using a rotary evaporator until the solid content concentration reached 0.40%, and was used in the subsequent steps. Hereinafter, the cellulose nanofiber aqueous dispersion with a solids concentration of 0.40% is also referred to as "cellulose nanofiber aqueous dispersion A."

[0060] Highly purified fish-derived type I antifreeze protein (manufactured by Nichirei, equivalent to an antifreeze agent) was added to the above cellulose nanofiber aqueous dispersion A at a concentration of 0.08% relative to the total mass of cellulose nanofiber aqueous dispersion A, and the mixture was stirred with a magnetic stirrer.

[0061] [Process A] Cellulose nanofiber aqueous dispersion A with added antifreeze protein was poured into a circular petri dish with a diameter of 10 cm. In this petri dish, 100 g of 1.0 M hydrochloric acid was gently poured down the wall and allowed to stand for 1 hour. The dispersion was physically gelled to form a gel, and the gel was 1 cm thick. In Table 1 below, gelation using hydrochloric acid is abbreviated as "Method 1." The gel was then cut into 1 cm cubes and subjected to step B.

[0062] [Process B] Solvent replacement was carried out using a specific mixed solvent in which the mixture ratio of t-butyl alcohol and water was 70:30 by mass. The solvent exchange was carried out by immersing the gel (1 cm square) in a sufficient amount of the specific mixed solvent and shaking it slowly several times. Specifically, the solvent exchange was carried out for 4 hours or more four times.

[0063] [Process C] The gelled product obtained in the solvent substitution step was immersed in liquid nitrogen (-196°C) and frozen to obtain a frozen gelled product.

[0064] [Process D] The frozen gel was dried by sublimation to remove the solvent using a vacuum dryer (Tokyo Rikakikai Co., Ltd.) to obtain an aerogel (porous body). The sublimation drying was carried out for 8 hours while maintaining the inside of the vacuum dryer at 10°C and a pressure of 10 Pa.

[0065] <Example 2> A porous body was obtained in the same manner as in Example 1, except that 100 g of 0.1 M aluminum chloride was used instead of "100 g of 1.0 M hydrochloric acid" used in step A.

[0066] <Examples 3 to 5> A porous body was obtained in the same manner as in Example 1, except that a specific mixed solvent having a mass ratio of TBA to water (TBA:water) shown in Table 1 below was used.

[0067] <Example 6> A porous body was obtained in the same manner as in Example 1, except that in step C, freezing was performed in a freezer at -18°C instead of immersion in liquid nitrogen (-196°C).

[0068] <Example 7> In step D, the porous body of Example 7 was obtained in the same manner as in Example 1, except that the pressure maintained during sublimation drying was changed to 100 Pa.

[0069] <Comparative Example 1> The porous body of Example 7 was obtained in the same manner as in Example 1, except that the steps A and B were not performed.

[0070] <Comparative Examples 2 to 3> A porous body was obtained in the same manner as in Example 1, except that a specific mixed solvent having a mass ratio of TBA to water (TBA:water) shown in Table 1 below was used.

[0071] <Comparative Example 4> A porous body of Example 7 was obtained in the same manner as in Example 1, except that step C was not performed and drying at normal pressure was performed instead of sublimation drying.

[0072] <Comparative Example 5> A porous body of Example 7 was obtained in the same manner as in Example 1, except that drying at normal pressure was performed instead of sublimation drying.

[0073] <Comparative Example 6> Example 7 described in paragraph

[0067] of Japanese Patent No. 6212622 was repeated.

[0074] <Measurement and Evaluation> [Measurement of fiber diameter] The fiber diameters of the porous bodies of the examples and comparative examples were measured by the method described above, and the results are shown in Table 1 below.

[0075] [Transmittance evaluation] The transmittance of the porous bodies in the examples and comparative examples was measured using a UV-Vis-NIR spectrophotometer V-660 equipped with an automatic absolute reflectance measurement unit ARMN-735 manufactured by JASCO Corporation. During the measurement, the sample was placed close to an integrating sphere to measure the total light transmittance, and the transmittance was evaluated based on the transmittance at 550 nm. The results are shown in Table 1 below.

[0076] [Table 1]

[0077] From the results shown in Table 1 above, it was found that when steps A and B were not carried out, the transmittance of the porous body was 0%, resulting in poor transparency (Comparative Example 1). In addition, when the mixed solvent used to replace the water contained in the gelled material had a mass ratio of TBA and water (TBA:water) of 39:61, the transmittance of the porous body was less than 30%, indicating poor transparency (Comparative Example 1). Furthermore, when the mixed solvent used to replace the water contained in the gelled material had a mass ratio of TBA and water (TBA:water) of 100:0, the transmittance of the porous body was 5%, indicating poor transparency (Comparative Example 3). In addition, in regard to step D, when normal pressure drying was used instead of sublimation drying, the transmittance of the porous body was 0%, indicating poor transparency, regardless of whether step C was performed or not (Comparative Examples 4 and 5). Moreover, in Example 7 described in paragraph

[0067] of Japanese Patent No. 6212622, the transmittance of the porous body was 0%, and it was found to be poor in transparency (Comparative Example 6).

[0078] In contrast, in all of Examples 1 to 7 in which steps A to D were carried out, the fiber diameter of the porous body was 3 to 40 nm, and the transmittance was 30% or more, indicating excellent transparency. In particular, a comparison between Example 1 and Example 3 revealed that the transparency of the porous body was higher when the mixed solvent used to replace the water contained in the gelled material had a TBA to water mass ratio (TBA:water) of 60:40 to 99:1. Furthermore, a comparison of Examples 1, 4, and 5 revealed that the transparency of the porous body was further increased when the mixed solvent used to replace the water contained in the gelled material had a TBA to water mass ratio (TBA:water) of 85:15 to 95:5.

Claims

1. A method for producing a porous body having a fiber diameter of 3 to 40 nm using cellulose nanofibers as a raw material, comprising the steps of: A step A of gelling the cellulose nanofiber aqueous dispersion to obtain a gelled product; a step B of replacing the water contained in the gel with a mixed solvent having a mass ratio of t-butyl alcohol to water of 41:59 to 99:1; A step C of freezing the gelled material after the step B to obtain a frozen gelled material; and a step D of sublimating and drying the frozen gelled material.

2. The method for producing a porous body according to claim 1, wherein a mass ratio of t-butyl alcohol to water in the mixed solvent is 60:40 to 99:

1.

3. The method for producing a porous body according to claim 1, wherein a mass ratio of t-butyl alcohol to water in the mixed solvent is 85:15 to 95:5.

Citation Information

Patent Citations

  • Physical gel and method of producing the same

    JP2012001626A